Increase brand loyalty through brand benefits on domestic products in Indonesia - Dirgantari, Puspo Dewi; Yusary, Sarah; Wibowo, Lili Adi; Hidayat, Yusuf Murtadlo; Soegoto , Eddy Soeryanto; Mahphoth, Mohd Halim; Martha, Jefry Aulia (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
This study aims to analyze the effect of brand benefits in increasing brand loyalty of domestic products in Indonesia, a study on users of Indonesian domestic skincare products. A quantitative approach was used in the research, by distributing a comprehensive questionnaire and literature. The number of samples obtained was 200 people and Structural Equation Modeling was used in the data analysis technique. The results of the study show that the description of brand benefits and brand loyalty is quite high and brand benefits have an effect on brand loyalty. The dimension of brand benefit that contributes the most is emotional benefit, while the dimension of brand benefit that contributes the least and needs to be improved is social benefit.